PrEP (non-)adherence among men who have sex with men in Portugal: A qualitative study - Pinheiro, G. G.; Moleiro, C.; Rodrigues, D. L. (XXI PhD Meeting in Psychology I Psychology in the XXI century: Science, practice and society, 2026)
Portugal continues to report disproportionately high rates of new HIV diagnoses within Western Europe. Although oral pre-exposure prophylaxis (PrEP) is a proven biomedical HIV prevention strategy, uptake and adherence levels remain below the UNAIDS target. This study examined how men who have sex with men (MSM) in Portugal – both PrEP users and non-users – in different stages of the PrEP care continuum perceive PrEP. Seventeen semi-structured interviews were conducted to explore perceived advantages and disadvantages of PrEP, social meanings attached to its use, and experiences with healthcare services. Data was analyzed using qualitative content analysis, informed by consensual qualitative research procedures. Findings highlighted the role of the community in raising PrEP awareness and uptake, including community-based services and peer networks. However, the limited availability of community-based services outside major urban centers created barriers for individuals living in rural areas. Stigma hindered PrEP promotion, affecting users’ sexual and romantic interactions for its association with promiscuity, or perceived as intended only for cis-MSM. In this context, PrEP stigma was more salient among those with intersecting marginalized identities, such as migrant individuals. Moreover, a high perception of HIV risk emerged as a key factor driving PrEP awareness, uptake, and adherence, wherein a low perception of risk was associated with reduced willingness to use PrEP and with PrEP discontinuation. By situating PrEP experiences within the Portuguese healthcare context, this study identifies structural and sociocultural barriers limiting equitable access and sustained use. The findings highlight the need to expand community-based services beyond urban areas, implement targeted stigma-reduction strategies, and adopt risk-perception–informed counseling approaches. As Portugal moves toward integrating PrEP delivery into primary care, these insights offer practical guidance for improving implementation and reducing health disparities among MSM. Future quantitative research with larger and more diverse samples could further strengthen understanding of these issues.